2009
DOI: 10.1080/00015458.2009.11680404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors and Severity of a Life Threatening Surgical Emergency: Fournier’s Gangrene (A Report of 15 Cases)

Abstract: Aggressive surgical debridement and combined antibiotherapy are essential in the management of Fournier's gangrene. FGSI and BSA are useful to assess the severity and prognosis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
2
19
0
2
Order By: Relevance
“…Its association with increased mortality is controversial. [8161718] There is similar uncertainty about the association of age and mortality. [819202122] Ischemic heart disease and CRF, specially hemodialysis dependence, seem to be significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Its association with increased mortality is controversial. [8161718] There is similar uncertainty about the association of age and mortality. [819202122] Ischemic heart disease and CRF, specially hemodialysis dependence, seem to be significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Kabay and colleagues analyzed patients using this index and showed those with FGSI greater than 10.5 had 96% mortality whereas those with a score less than 10.5 had 96% survival [Kabay et al 2008]. Kara and colleagues found that FGSI scores of at least 7 affected mortality rates with statistical significance (p < 0.05) and Altarac and colleagues noted that FGSI scores were significantly higher among nonsurvivors (11 versus 5, p < 0.0001) [Kara et al 2009;Altarac et al 2012]. However, controversy exists regarding the accuracy of FGSI, as Tuncel and colleagues and Janane and colleagues argued the index cannot be relied upon to predict survival [Tuncel et al 2006;Janane et al 2011].…”
Section: Investigationsmentioning
confidence: 99%
“…The presence of severe sepsis on admission has been significantly associated with mortality [Kara et al 2009;Altarac et al 2012]. Additionally, the volume of necrosis appears to be a prognostic factor as some studies show patients with a gangrenous area less than 3% of the body surface rarely die, whereas patients presenting with a gangrenous area of 5% body surface area or more have a worse prognosis [Dahm et al 2000;Horta et al 2009;Janane et al 2011].…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations